The Role of Social-Commerce, Influencers, and Diderot Effect on Consumers’ Impulsive Buying: A Systematic Review - Iwan Sukmana; Ibnu Aditya Karana; Wilfried Agusman; Intan Wahyuningtias; Lela Nurlaela Wati (Research Synergy Foundation, 2026)
The increasingly intensive integration of social media and digital commerce has transformed impulsive buying from an individual behavior into a phenomenon structurally embedded within the digital consumption ecosystem. This systematic literature review aims to synthesize theoretical and empirical evidence on the roles of social commerce, influencer-driven persuasion, and the Diderot Effect in shaping impulsive buying in contemporary digital markets. The study applies the PRISMA method by examining 26 reputable Scopus-indexed journal articles published between 2021 and 2026. Articles were selected through a multi-stage screening process based on inclusion criteria, methodological quality, thematic relevance, and subsequently analyzed using a thematic synthesis approach. The review findings indicate that impulsive buying is a socio-technical outcome simultaneously produced by algorithmic design, social interaction, and post-purchase consumption dynamics. Social commerce features such as live streaming, short-form videos, social proof cues, and in-app purchasing mechanisms function as primary stimuli that intensify emotional arousal, hedonic pleasure, and fear of missing out. Influencers further amplify these effects through perceived credibility, parasocial relationships, and identity-based narratives. Moreover, the Diderot Effect is identified as a key explanatory mechanism linking initial impulsive purchases to sequential and excessive consumption. This review identifies theoretical gaps, methodological limitations, and ethical concerns, and proposes a future research agenda that emphasizes integrative models, longitudinal designs, and responsible social commerce governance.